Case Study On VADS Berhad As A Leading ICT Service Provider - Adam, Norazimah (2007)
To study the ICT industry especially in Malaysia with special attention will be on VADS Company whereby the attempt is to understand it strategy, growth and its future prospect in both domestic and international market as a Leading Managed ICT Service Provider.